Trade-off between forest conservation and agricultural expansion in Gura-ferda district, Southwest Ethiopia - Tsegaye, Henok; Tesfaye, Yemiru; Abebaw, Degnet; Kassa, Habtemariam; Abdelkadir, Abdu; Gizachew, Kebede (International Journal of Agricultural Research, Innovation and Technology, 2022)
Agricultural expansion is one of the main drivers of deforestation in Ethiopia. This study was therefore carried out to examine the trade-off between forest and agricultural land uses in Guraferda district, southwest Ethiopia. Data to estimate economic values of land use were derived from the household surveys, key informant interviews, and focus group discussions. The household surveys were carried out in four purposively selected kebeles. Within the selected Kebeles, a total of 186 sample households were selected randomly. In addition, this study used Remote Sensing (RS) to detect and quantify LULC changes that occurred in the district throughout a thirty-year study period. The study employed by Excel 2013 for solving a cost –benefit analysis and ERDAS Imagine 9.1 for image processing. The finding revealed that an expansion of agriculture/settlement and shrinkage of forest and shrub land over the last thirty-year. The forest and shrub land use decreased by 0.43 and 2.42% ha year-1, respectively, whereas agriculture/settlement and grassland increased by 9.1 and 0.64% ha year-1, respectively over the same period. The deforestation rate is estimated at 425 ha year-1 in the study area. Analysis of trade-off provides estimated forgone earnings of about ETB 79,138 ETB (1665.3 USD ha-1) and ETB 258,298.10 (5,435.5 USD ha-1) from forest conservation and crop production, respectively assuming a 20-year planning horizon and a 10% discount rate. The 425 ha of annual deforestation entails a loss of ETB 33,633,650 (707,779 USD year-1) from forest conservation and a gain of 109,776,692.5 ETB (2,310,115.5 USD) agricultural activity. Int. J. Agril. Res. Innov. Tech. 12(1): 45-55, June 2022